Identifying Unmarked Crosswalks at Bus Stops in Vancouver, Canada - Kate Hosford; Sarah Tremblay; Meghan Winters (Findings)
Taking transit to and from a destination typically involves crossing the street, however, not all bus stops have a marked pedestrian crossing. This study aimed to 1) identify bus stops in Vancouver, Canada with unmarked crosswalks and 2) assess whether unmarked crosswalks at bus stops are inequitably distributed across the city. Of the 1,892 bus stops in Vancouver, 8% (n=151) did not have a traffic signal or marked crosswalk at the nearest intersection. Unmarked crossings were more likely to be at bus stops in higher income neighbourhoods compared to bus stops in lower income neighbourhoods.